Exploring Chemistry Teachers' Awareness of FabLab for Transformative Educational Practices - Khefrianti, Syinta; Rustaman, Nuryani; Kadarohman, Asep; Wiji, Wiji (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
Learning chemistry materials using 2D media is currently unable to provide a clear picture of some abstract and microscopic chemical content. Several studies show that many students have difficulty with chemistry because they cannot visualize structures and processes at the submicroscopic level and relate them to other levels of chemical representation. The purpose of this study was to determine the teachers' understanding of new technology that can be used to help students translate 2D into 3D in real form, namely using FabLab. This research is descriptive qualitative research with the research subjects 39 high school teachers and vocational school teachers in West Java. There are three stages in this research, data reduction, data presentation and conclusion drawing. The results showed that all teachers do not know or understand FabLab, although there are teachers who have attended training related to FabLab.Only 23% of teachers are aware of 3D printing but they do not know what is meant by FabLab. There are two schools that have 3D printing facilities, but they are not utilized, one of the reasons being the lack of technological mastery. This research is useful in designing professional development training for chemistry teachers in the field of technology, specifically in the utilization of FabLab.